Application of Inquiry Learning Model to Improve Learning Activeness of Class V Natural Resources Conservation Efforts - Siti Yuhanir (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve the activeness of students in the subject matter of Natural Resources Conservation Efforts using inquiry learning models. The research conducted was a Classroom Action Research (PTK) in 3 cycles, with each cycle consisting of 1 meeting. The stages of each cycle are planning, implementing, observing, and reflecting. In cycle 1, students who were declared active after observation were 64.58%. In cycle 2, students who were declared active after observation were 88.15 percent. In cycle 3 students who were active after observation were 94.1%. These results indicate that the inquiry learning model can increase the activeness of students, especially the content of science lessons on Natural Resources Conservation Efforts for grade IV SDN Blondo 3.